Mixed cement material and preparation method thereof
By mixing the machined sand filter cake with cement and using steps such as drying, crushing and screening and ultrasonic treatment, the problems of complex processes and high energy consumption in the existing technology are solved, and efficient and environmentally friendly mixed cement preparation is achieved, reducing cement costs and carbon emissions.
Patent Information
- Application Number
- CN202411904770.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the process of using solid waste to prepare mixed cement is complex, the additives are used in large amounts, the energy consumption is high, and the impact of raw material particle size and specific surface area on product performance is insufficient.
By mixing the machined sand filter cake with cement, using drying, crushing and screening and sonication steps, a mixed cement material is prepared, which avoids the use of chemical agents and calcination steps, simplifies the process flow, and reduces energy consumption.
It realizes efficient preparation of mixed cement, reduces cement costs, alleviates the problem of storage of machined sand filter cakes and the high carbon emission problems of cement production, and has excellent product performance and low energy consumption.
Smart Images

Figure CN119774942A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste construction material conversion, and in particular to a mixed cement material and a preparation method thereof. Background Art
[0002] With the booming construction industry, the demand for sand and gravel aggregates has continued to grow, resulting in a shortage of natural sand resources and accelerating the development of the machine-made sand industry. In the process of wet production of machine-made sand, stone powder will inevitably be produced in the crushing process, and these stone powders will be tightly attached to the surface of sand and gravel particles. In order to remove these impurities, a series of processing steps such as water washing, precipitation and filter pressing are introduced into the production process, and finally the stone powder and other impurities are separated in the form of filter cakes. According to statistics, my country's annual machine-made sand production has exceeded 17 billion tons, producing a large number of machine-made sand filter cakes.
[0003] At present, the main way to deal with machine-made sand filter cakes is open-air storage, which brings many environmental and ecological problems that cannot be ignored. First of all, machine-made sand filter cakes occupy a large amount of valuable land resources, increase the operating costs of enterprises, and restrict the normal production activities of enterprises. In addition, machine-made sand filter cakes stored in the open air are easily affected by environmental factors, such as dust pollution under the action of wind, and natural disasters such as landslides caused by rain erosion, which pose a direct threat to the living environment of surrounding residents and also bury major safety hazards. Therefore, it is particularly urgent and important to explore an efficient and environmentally friendly way to utilize machine-made sand filter cakes.
[0004] At present, there are few patents related to the preparation of mixed cement using machine-made sand filter cake, and the theoretical and practical development is still imperfect. Chinese patent CN 112960919 A discloses a method for preparing cement admixtures using sand washing sludge. The sand washing sludge in the process of machine-made sand production is used as raw material. Through drying, mixing, calcining, ball milling and other processes, the sand washing sludge is converted into cement admixtures. The 28-day compressive strength of the finished product reaches 33.7 MPa. However, the production cost of the calcination link in this process is relatively high. Chinese patent CN114394770 A discloses a method for preparing tungsten tailings cement admixtures. The activity of tungsten tailings is improved through chemical excitation, calcination and mechanical activation, and used for the preparation of cement admixtures. The resulting product has a 28-day compressive strength of 48.0 MPa. However, this process also involves high-cost links such as chemical treatment and calcination.
[0005] In summary, the current methods of using solid waste to prepare blended cement have the following problems: ① The preparation process is lengthy and complicated; ② Additional minerals or chemicals are often required to adjust performance; ③ The activity of raw materials needs to be increased through high-energy consumption methods such as calcination, resulting in high overall costs; ④ There is insufficient research on the impact of parameters such as raw material particle size and specific surface area on product performance. Summary of the invention
[0006] In view of the above-mentioned deficiencies, the object of the present invention is to provide a mixed cement material and a preparation method thereof, so as to solve the problems of the prior art of preparing mixed cement using solid waste, such as complex process, large amount of additives used, and high energy consumption.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions: In one aspect, the present invention provides a mixed cement material, comprising machine-made sand filter cake and cement, wherein the mass ratio of the machine-made sand filter cake to the cement is (5-20): (80-95).
[0008] Preferably, the mass ratio of machine-made sand filter cake to cement is (5-15):(85-95).
[0009] Preferably, the machine-made sand filter cake comprises SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, and Na2O; the mass ratios of SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, and Na2O are (50-55): (10-20): (5-10): (5-6): (6-7): (3-4): (2-3).
[0010] Preferably, the particle size of the machine-made sand filter cake is ≤0.075 mm and the specific surface area is ≥250 m 2 / kg.
[0011] Preferably, the cement is Portland cement.
[0012] Preferably, the silicate cement is one or more of 52.5 grade silicate cement, 42.5 grade silicate cement, and 32.5 grade silicate cement.
[0013] In a second aspect, the present invention provides a method for preparing a mixed cement material, comprising the following steps: S1, drying the machine-made sand filter cake to obtain the first material; S2, crushing and screening the first material to obtain a second material; S3, subjecting the second material to ultrasonic treatment to obtain a third material; S4. Evenly mix the third material and cement to obtain the mixed cement material.
[0014] Preferably, in step S1, the drying temperature is 90°C to 110°C, and the drying time is 20 h to 30 h.
[0015] Preferably, in step S2, the sieve used for the screening process is 200-300 mesh.
[0016] Preferably, in step S3, the ultrasonic frequency of the ultrasonic treatment is 35 kHz to 45 kHz, and the ultrasonic treatment time is 20 min to 40 min.
[0017] Preferably, the crushing and screening process of step S2 includes: passing the first material through a 200-300 mesh sieve to obtain a second material; and re-crushing and screening the material on the sieve to obtain the material under the sieve.
[0018] The beneficial effects of the present invention are: The present invention uses machine-made sand filter cake to replace standard cement to prepare mixed cement, which not only saves cement costs, but also alleviates the storage problem of machine-made sand filter cake and the high carbon emission problem of cement production. At the same time, the present invention avoids the use of chemical agents and omits the calcination step. The preparation method is simple, energy consumption is low, and the finished product performance is excellent, achieving a dual improvement in efficiency and quality.
[0019] The invention increases the specific surface area of the machine-made sand filter cake by ultrasonic treatment, thereby promoting the progress of cement hydration reaction, so that the performance of the prepared mixed cement is better under the same machine-made sand filter cake dosage. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0021] Figure 1 The present invention is a flow chart of the preparation process of a mixed cement material. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In response to the land resource and environmental problems caused by the storage and treatment of machine-made sand filter cakes, this application provides a method for preparing mixed cement in a green and efficient manner using machine-made sand filter cakes as raw materials. The main component of machine-made sand filter cakes is silicon-aluminum. As a cement mixed material to replace part of the cement, it can not only relieve the pressure on the storage yard, but also reduce the production of cement clinker and reduce the CO2 emissions of the cement production industry. It is of great significance to alleviate global warming and promote the development of green building materials. Therefore, the application of machine-made sand filter cakes in the field of cement production is not only a resource utilization of waste, but also a practice of the concept of sustainable development.
[0024] The chemical composition of the machine-made sand filter cake used in the following examples and comparative examples is: SiO2 52.32 wt%, Al2O3 15.02 wt%, Fe2O3 9.92 wt%, CaO 5.99 wt%, MgO 6.59 wt%, K2O 3.10 wt%, Na2O 2.08 wt% and a small amount of other elements.
[0025] Example 1 A mixed cement material, the preparation method is as follows Figure 1 As shown, the following steps are included: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0026] S2. Crushing and screening: Use a ball mill to grind the first material, and after passing it through a 200-mesh standard sieve, the product under the sieve is the second material, and the product on the sieve is further crushed and closed-circuit screened.
[0027] S3, Ultrasound: The second material was dispersed in an ultrasonic device with a frequency of 40 kHz for 20 min to obtain a third material with a specific surface area of 256.5 m 2 / kg.
[0028] S4. Mixing: Evenly mix 5 wt% of the third material and 95 wt% of PO 52.5 silicate cement to obtain a mixed cement product.
[0029] Example 2 A mixed cement material, the preparation method comprises the following steps: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0030] S2. Crushing and screening: Use a ball mill to grind the first material, and after passing it through a 200-mesh standard sieve, the product under the sieve is the second material, and the product on the sieve is further crushed and closed-circuit screened.
[0031] S3, Ultrasound: The second material was dispersed in an ultrasonic device with a frequency of 40 kHz for 20 min to obtain a third material with a specific surface area of 256.5 m 2 / kg.
[0032] S4. Mixing: Evenly mix 10 wt% of the third material and 90 wt% of PO 52.5 silicate cement to obtain a mixed cement product.
[0033] Example 3 A mixed cement material, the preparation method comprises the following steps: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0034] S2. Crushing and screening: Use a ball mill to grind the first material, and after passing it through a 200-mesh standard sieve, the product under the sieve is the second material, and the product on the sieve is further crushed and closed-circuit screened.
[0035] S3, Ultrasound: The second material was dispersed in an ultrasonic device with a frequency of 40 kHz for 20 min to obtain a third material with a specific surface area of 256.5 m 2 / kg.
[0036] S4. Mixing: Evenly mix 15 wt% of the third material and 85 wt% of PO 52.5 silicate cement to obtain a mixed cement product.
[0037] Example 4 A mixed cement material, the preparation method comprises the following steps: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0038] S2. Crushing and screening: Use a ball mill to grind the first material, and after passing it through a 300-mesh standard sieve, the product under the sieve is the second material, and the product on the sieve is further crushed and closed-circuit screened.
[0039] S3, Ultrasound: The second material was dispersed in an ultrasonic device with a frequency of 40 kHz for 20 min to obtain a third material with a specific surface area of 260.5 m 2 / kg.
[0040] S4. Mixing: Evenly mix 10 wt% of the third material and 90 wt% of PO 52.5 silicate cement to obtain a mixed cement product.
[0041] Comparative Example 1 A mixed cement material, the preparation method comprises the following steps: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0042] S2. Crushing and screening: Use a ball mill to grind the first material, and after passing it through a 200-mesh standard sieve, the product under the sieve is the second material, and the product on the sieve is further crushed and closed-circuit screened.
[0043] S3, Ultrasound: The second material was dispersed in an ultrasonic device with a frequency of 40 kHz for 20 min to obtain a third material with a specific surface area of 256.5 m 2 / kg.
[0044] S4. Mixing: Evenly mix 25 wt% of the third material and 75 wt% of PO 52.5 silicate cement to obtain a mixed cement product.
[0045] Comparative Example 2 A mixed cement material, the preparation method comprises the following steps: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0046] S2, Ultrasound: The first material was dispersed in an ultrasonic device with a frequency of 40 kHz for 20 min to obtain a second material with a specific surface area of 233.7 m 2 / kg.
[0047] S3, mixing: 10 wt% of the second material and 90 wt% of PO 52.5 silicate cement are uniformly mixed to obtain a mixed cement product.
[0048] Comparative Example 3 A mixed cement material, the preparation method comprises the following steps: S1. Drying: The machine-made sand filter cake is placed in a blast drying oven at 105°C for 24 hours to obtain the first material.
[0049] S2. Crushing and screening: The first material is ground using a ball mill and passed through a 200-mesh standard sieve. The product under the sieve is the second material, and its specific surface area is 248.3 m 2 / kg, and the product on the sieve is further crushed and screened in a closed circuit.
[0050] S3, mixing: 10 wt% of the second material and 90 wt% of PO 52.5 silicate cement are uniformly mixed to obtain a mixed cement product.
[0051] The compressive strength of the mixed cement materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were tested respectively, and the results are shown in Table 1.
[0052] Table 1 Compressive strength test results of Examples 1 to 4 and Comparative Examples 1 to 3 (water / mixed cement = 0.33)
[0053] As shown in Table 1, the mixed cement prepared in the embodiment of the present invention has a relatively good development of slurry compressive strength, and the loss rate of 28-day compressive strength is lower than the reduction of PO 525 cement, indicating that in the slurry of the mixed cement prepared in the embodiment, the machine-made sand filter cake plays a role in compensating strength. This is because the alkaline environment of cement hydration has an alkali-stimulating effect on the hydration activity of the machine-made filter cake, and the machine-made sand filter cake itself has a certain filling effect. However, the mixed cement prepared in the comparative example has a relatively poor development of slurry compressive strength, and the loss rate of 28-day compressive strength is higher than the reduction of PO 525 cement, indicating that the machine-made sand filter cake in the mixed cement cannot play a role in compensating strength if the machine-made sand filter cake dosage is too high or the particles are too coarse. The strength decreases when the machine-made sand filter cake dosage is too high, because the alkalinity of the hydration environment decreases after the cement dosage is too low, and the activity of the machine-made sand filter cake stimulated by the low alkalinity is not enough to compensate for the strength development; the particles are too coarse and the strength decreases, because the rate at which the large-particle machine-made sand filter cake is stimulated to have hydration activity is low, resulting in its poor effect of compensating for strength development.
[0054] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For details not described in individual embodiments, reference may be made to the description in other embodiments.
[0055] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A mixed cement material, characterized in that: The invention comprises machine-made sand filter cake and cement, wherein the mass ratio of the machine-made sand filter cake to the cement is (5-20): (80-95).
2. The mixed cement material according to claim 1, characterized in that: The mass ratio of the machine-made sand filter cake to the cement is (5-15):(85-95).
3. The mixed cement material according to claim 1, characterized in that: The machine-made sand filter cake includes SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, and Na2O; the mass ratio of SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, and Na2O is (50-55): (10-20): (5-10): (5-6): (6-7): (3-4): (2-3).
4. The mixed cement material according to claim 1, characterized in that: The particle size of the machine-made sand filter cake is ≤0.075 mm, and the specific surface area is ≥250 m 2 / kg.
5. The mixed cement material according to claim 1, characterized in that: The cement is silicate cement.
6. The mixed cement material according to claim 5, characterized in that: The silicate cement is one or more of 52.5 grade silicate cement, 42.5 grade silicate cement and 32.5 grade silicate cement.
7. A method for preparing a mixed cement material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, drying the machine-made sand filter cake to obtain the first material; S2, crushing and screening the first material to obtain a second material; S3, subjecting the second material to ultrasonic treatment to obtain a third material; S4. Evenly mix the third material and cement to obtain the mixed cement material.
8. The method for preparing a mixed cement material according to claim 7, characterized in that: In step S1, the drying temperature is 90°C to 110°C, and the drying time is 20 h to 30 h.
9. The method for preparing a mixed cement material according to claim 7, characterized in that: In step S2, the sieve used in the screening process is 200-300 mesh.
10. The method for preparing a mixed cement material according to claim 7, characterized in that: In step S3, the ultrasonic frequency is 35 kHz to 45 kHz, and the ultrasonic treatment time is 20 min to 40 min.
Citation Information
Patent Citations
Method for preparing cement mixture from sand washing sludge
CN112960919A
Preparation method of tungsten tailing cement admixture
CN114394770A